Performance and bacterial community structure in three autotrophic submerged biofilters operated under different conditions. Issue 8 (25th March 2018) - García‐Ruiz, María J; Maza‐Márquez, Paula; González‐Martínez, Alejandro; Campos, Elena; González‐López, Jesús; Osorio, Francisco
Abstract: BACKGROUND: Autotrophic nitrogen removal was evaluated in three bench‐scale bioreactors filled with Filtralite. This configuration is an alternative to the conventional technologies for nitrogen removal. One of the main problems associated with these new technologies, based on anammox (anaerobic ammonium oxidation) processes, is the stability of biomass. In this research the bioreactors' performance and stability of the bacterial community were studied under the following conditions: dissolved oxygen (0.3–1.5 mg O2 L ‐1 ), influent N‐NH4 + concentration 246 mg L ‐1, and different NO2 ‐ ‐N concentrations (106.5, 30 and 0 mg NO2 ‐ ‐N L ‐1 ). RESULTS: Total nitrogen removal efficiencies were 80.78% and 92% for bioreactors operated under microaerobic conditions (less than 1.5 mg O2 L ‐1 ) and 30 and 0 mg NO2 ‐ ‐N L ‐1, respectively. Bioreactors attained maximum efficiency after about 80 days. In contrast, the total nitrogen removal efficiency was only 69.57% for the bioreactor operated under anoxic conditions and 106.5 mg NO2 ‐ ‐N L ‐1, but maximum efficiency was achieved after approximately 30 days. The presence of oxygen increased the relative abundance of ammonium‐oxidizing bacteria, which reached 6% in bioreactors with a low dissolved oxygen concentration. The relative abundance of Candidatus Brocadia remained stable in all bioreactors. CONCLUSIONS: The results showed that nitrite and anoxic conditions led to quicker start‐up of a single reactor process during the initial days of operation. The combination of quantitative real‐time PCR (qPCR) and Illumina sequencing revealed that the operational conditions changed the bacterial community structure. The relative abundance of Candidatus Brocadia remained stable in all bioreactors, whereas significant differences were detected for Nitrosomonas . © 2018 Society of Chemical Industry